Shear Strength and Behavior of High Strength Reinforced Concrete Beams without Stirrups - Saeed, Jalal Ahmad; Abubaker, Abbas Mohammed (Sulaimani Journal for Engineering Sciences, 2016)
This paper presents test results of twelve high strength reinforced concrete (HSRC) beams without stirrups which were tested to investigate their shear strength and behavior under loading. The shear behavior, ultimate load-carrying capacity, and mode of failure are presented. The applicability the ACI 318M-11, Modified Zsutty, and Sudheer et al, the influences of shear span to effective depth ratio (a/d) and compressive strength (fc') on their shear strength are also presented. It is found that, In general, with increasing each of compressive strength and (a/d) ratio the failure loads and consequently the shear strength of the beams didn't increase significantly. It is also found that ACI 318 M-11 overestimates for some test results (unsafe) while Sudheer et al equation underestimates for all test results excessively. However, Modified Zsutty equation underestimates the tested values for all the tested beams and could estimate shear capacity satisfactorily within a reasonable factor of safety. A regression equation was proposed and it was found to be more reliable and safe in predicting shear strength of high strength reinforced concrete beams.
Keywords: shear strength; high strength; Stirrups